1992
DOI: 10.1109/72.125867
|View full text |Cite
|
Sign up to set email alerts
|

Information geometry of Boltzmann machines

Abstract: A Boltzmann machine is a network of stochastic neurons. The set of all the Boltzmann machines with a fixed topology forms a geometric manifold of high dimension, where modifiable synaptic weights of connections play the role of a coordinate system to specify networks. A learning trajectory, for example, is a curve in this manifold. It is important to study the geometry of the neural manifold, rather than the behavior of a single network, in order to know the capabilities and limitations of neural networks of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
156
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 20 publications
0
156
0
Order By: Relevance
“…In particular, some authors [6,51,54] reported applications of information geometry to Bayesian statistics [32] and Bartlett correction [15]. In addition, we must say that information geometry is applied not just to statistics and information theory but also to combinatorics of neural networks and psychology [5], physics [20] and many other fields.…”
Section: Information Geometrymentioning
confidence: 99%
“…In particular, some authors [6,51,54] reported applications of information geometry to Bayesian statistics [32] and Bartlett correction [15]. In addition, we must say that information geometry is applied not just to statistics and information theory but also to combinatorics of neural networks and psychology [5], physics [20] and many other fields.…”
Section: Information Geometrymentioning
confidence: 99%
“…As shown in [32], G θ and G η are mutually inverse matrices, i.e., J g IJ g JK = δ I K , where δ I K = 1 if I = K and zero if I = K. Next, we will develop the two propositions to compute G θ and G η generally. Note that Proposition 2.1 is a generalization of Theorem 2 in [33].…”
Section: B Fisher Information Matrix For Parametric Coordinatesmentioning
confidence: 94%
“…In the present study, we investigate the information geometry of RoBMs along the line of research by Amari [3]. First, we reveal that RoBMs form an exponential family and determine the Fisher metric, natural and expectation coordinate systems, and the potential functions of RoBMs.…”
Section: Introductionmentioning
confidence: 92%
“…Thus RoBMs realize more flexible distributions than CBMs. Amari has investigated Boltzmann machines through information geometry [2,3]. Information geometry is an excellent method for analyzing stochastic models [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation